Mifepristone prevents stress-induced apoptosis in newborn neurons and increases AMPA receptor expression in the dentate gyrus of C57/BL6 mice. - María Llorens-Martín (Public Library of Science (PLoS), 2011)
Chronic stress produces sustained elevation of corticosteroid levels, which is why it is considered one of the most potent negative regulators of adult hippocampal neurogenesis (AHN). Several mood disorders are accompanied by elevated glucocorticoid levels and have been linked to alterations in AHN, such as major depression (MD). Nevertheless, the mechanism by which acute stress affects the maturation of neural precursors in the dentate gyrus is poorly understood. We analyzed the survival and differentiation of 1 to 8 week-old cells in the dentate gyrus of female C57/BL6 mice following exposure to an acute stressor (the Porsolt or forced swimming test). Furthermore, we evaluated the effects of the glucocorticoid receptor (GR) antagonist mifepristone on the cell death induced by the Porsolt test. Forced swimming induced selective apoptotic cell death in 1 week-old cells, an effect that was abolished by pretreatment with mifepristone. Independent of its antagonism of GR, mifepristone also induced an increase in the percentage of 1 week-old cells that were AMPA(+). We propose that the induction of AMPA receptor expression in immature cells may mediate the neuroprotective effects of mifepristone, in line with the proposed antidepressant effects of AMPA receptor potentiators.